2012
DOI: 10.1007/s10973-012-2354-y
|View full text |Cite
|
Sign up to set email alerts
|

MgO/CaO-loaded porous carbons for carbon dioxide capture

Abstract: Nanoporous carbons loaded with both MgO and CaO were prepared by a simple heating of mixtures consisting of poly(ethylene terephthalate) and natural dolomite. Preparations were carried out at temperatures ranging from 850 to 1,000°C that ensured complete thermal decomposition of the dolomite contained in the mixtures to the oxides. An influence of the PET/dolomite weight ratio and temperature of the preparation process on the porosity of the obtained composite products and on CaO and MgO crystallite sizes are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…The XRD pattern suggests that the PPAC sample has asymmetric peaks from 25-50 • Figure 8B depicts the pore size distribution for PPAC, PPAC-MS25, PPAC-MS 50 and PPAC-MS 100. All adsorbents had a similar peak at 32 Å. MgSiO3 impregnation enhances the mesopore and macropore from at 140-370 Å. Przepiórski, et al [63] reported carbon material coating with magnesium oxide capable of creating more mesopores under thermal treatment. Table S4 lists the textural characteristics for all absorbents on the total surface area, BET surface area, micropore surface area, total pore volume and micropore volume.…”
Section: Copper Removal Mechanisms and Materials Characterizationsmentioning
confidence: 98%
“…The XRD pattern suggests that the PPAC sample has asymmetric peaks from 25-50 • Figure 8B depicts the pore size distribution for PPAC, PPAC-MS25, PPAC-MS 50 and PPAC-MS 100. All adsorbents had a similar peak at 32 Å. MgSiO3 impregnation enhances the mesopore and macropore from at 140-370 Å. Przepiórski, et al [63] reported carbon material coating with magnesium oxide capable of creating more mesopores under thermal treatment. Table S4 lists the textural characteristics for all absorbents on the total surface area, BET surface area, micropore surface area, total pore volume and micropore volume.…”
Section: Copper Removal Mechanisms and Materials Characterizationsmentioning
confidence: 98%
“…Dolomite is an important material in various industries such as metallurgy, the production of paper, glass, fertilizer, cement, concrete, functional construction material, and pharmaceutical industries [2]. The dolomite-based sorbents are used in low temperatures to reduce the emission of pollutants such as carbon, sulfur and nitrogen oxides, hydrogen chloride, and fluoride [1,3,4]. The applications of dolomite depend on its physicochemical, structural, and thermodynamic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The first weight-loss stage was mainly attributed to the thermal degradation process of macromolecules owning long molecular chains and huge molecular weight breaking into shorter molecular chain fragments via the chain scission when samples were gradually heated up to a certain high temperature. 32 Subsequently, these fragments could be further thermal-oxidized into many smaller volatile products and solid residues after several steps because of the existence of oxygen. 24,[33][34][35] According to the above curves, some useful parameters such as the onset temperature (T onset ), mass loss rate, and corresponding temperature were acquired as summarized in Table IV.…”
Section: Article Wileyonlinelibrarycom/appmentioning
confidence: 99%